2014
DOI: 10.1007/s11356-014-3634-9
|View full text |Cite
|
Sign up to set email alerts
|

Content of lead and cadmium in aboveground plant organs of grasses growing on the areas adjacent to a route of big traffic

Abstract: The effect of traffic on the content of lead and cadmium in grass morphological parts—leaves, shoots, and inflorescences—was studied. The samples were taken on a part of the European route E30 (Siedlce by road). The following plants were tested: Dactylis glomerata, Arrhenatherum elatius, and Alopecurus pratensis. During the flowering of grasses, the plant material was collected at distances of 1, 5, 10, and 15 m from the edge of the road, on the strip of road with a length of 9 km. In the collected plant parts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…In Poland, the concentration of this chemical element varied between different species of grass in the range from 0.1 to 2.6 mg kg −1 DM, whereas for D . glomerata L., these values ranged from 0.05 to 0.80 mg kg −1 DM (Jankowski et al 2015). According to Kabata-Pendias (2004), the maximum limits of the content of different heavy metals in forage are as follows: < 100 mg Zn < 30 mg Cu < 20 mg Cr < 50 mg Ni < 10 mg Pb < 0.5 mg Cd kg −1 DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Poland, the concentration of this chemical element varied between different species of grass in the range from 0.1 to 2.6 mg kg −1 DM, whereas for D . glomerata L., these values ranged from 0.05 to 0.80 mg kg −1 DM (Jankowski et al 2015). According to Kabata-Pendias (2004), the maximum limits of the content of different heavy metals in forage are as follows: < 100 mg Zn < 30 mg Cu < 20 mg Cr < 50 mg Ni < 10 mg Pb < 0.5 mg Cd kg −1 DM.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that grass can grow very quickly, even in small areas, and that it is an all-season plant is a reason why it was used in some studies in a very successful way to monitor pollution (Olajire and Ayodele 1997; Garcia and Milan 1998; Lai and Chen 2004; Filipek-Mazur et al 2007; Cicek et al 2012). Emission of heavy metals (lead and cadmium) coming from roads can cause diverse pollution of grass species and their morphological parts (De Nicola et al 2003; Naszradi et al 2004; Jankowski et al 2015). …”
mentioning
confidence: 99%
“…In many cases dandelion is collected in fields close to roads with heavy traffic. Car traffic is a considerable source of heavy metals [20,21], which are believed to be very dangerous roadside pollutants [22,23]. In addition to lead and cadmium, believed to be an inseparable part of dust issued by motor vehicles, zinc and copper are among the most common soil and vegetation pollutants in the area of communication routes [24].…”
Section: Introductionmentioning
confidence: 99%
“…As the study result indicated there is no sampling sites recorded a lead and cadmium concentration beyond the world health organization (WHO) permissible limit of 100 and 3.12mg/kg respectively. 11,[13][14][15] An average soil lead and cadmium concentration in these studied sites was in the estimated natural concentration 35mg/Kg to 50mg/ Kg and 0.5mg/Kg to 5mg/Kg. However, the concentration of such a heavy metal in these sampling sites were below the world health organization permissible limit the soil sample taken from sampling site of roadside exposed to gasoline and vehicular emission shows a considerable difference in concentration of lead and cadmium in relative to the soil of non-gasoline area.…”
Section: Resultsmentioning
confidence: 99%